Reducing antimicrobial overuse through targeted therapy for patients with community-acquired pneumonia: a study protocol for a cluster-randomized factorial controlled trial (CARE-CAP) - Abhishek Deshpande; Ramara Walker; Rebecca Schulte; Andrea M. Pallotta; Larisa G. Tereshchenko; Bo Hu; Sameer S. Kadri; Michael Klompas; Michael B. Rothberg (Trials, 2023)
Abstract Background Community-acquired pneumonia (CAP) is a significant public health concern and a leading cause of hospitalization and inpatient antimicrobial use in the USA. However, determining the etiologic pathogen is challenging because traditional culture methods are slow and insensitive, leading to prolonged empiric therapy with extended-spectrum antibiotics (ESA) that contributes to increased hospital length of stay, and antimicrobial resistance. Two potential ways to reduce the exposure to ESA are (a) rapid diagnostic assays that can provide accurate results within hours, obviating the need for empiric therapy, and (b) de-escalation following negative bacterial cultures in clinically stable patients. Methods We will conduct a large pragmatic 2 × 2 factorial cluster-randomized controlled trial across 12 hospitals in the Cleveland Clinic Health System that will test these two approaches to reducing the use of ESA in adult patients (age ≥ 18 years) with CAP. We will enroll over 12,000 patients and evaluate the independent and combined effects of routine use of rapid diagnostic testing at admission and pharmacist-led de-escalation after 48 h for clinically stable patients with negative cultures vs usual care. We hypothesize that both approaches will reduce days on ESA. Our primary outcome is the duration of exposure to ESA therapy, a key driver of antimicrobial resistance. Secondary outcomes include detection of respiratory viruses, treatment with anti-viral medications, positive pneumococcal urinary antigen test, de-escalation by 72 h from admission, re-escalation to ESA after de-escalation, total duration of any antibiotic, 14-day in-hospital mortality, intensive care unit transfer after admission, healthcare-associated C. difficile infection, acute kidney injury, total inpatient cost, and hospital length-of-stay. Discussion Our study aims to determine whether identifying an etiological agent early and pharmacist-led de-escalation (calling attention to negative cultures) can safely reduce the use of ESA in patients with CAP. If successful, our findings should lead to better antimicrobial stewardship, as well as improved patient outcomes and reduced healthcare costs. Our findings may also inform clinical guidelines on the optimal management of CAP. Trial registration ClinicalTrials.gov NCT05568654 . Registered on October 4, 2022.